Modeling Krebs cycle from liver, heart and hepatoma mitochondria, supported Complex I as target for specific inhibition of cancer cell proliferation - Hernández-Esquivel, Luz; Del Mazo-Monsalvo, Isis; Pacheco-Velázquez, Silvia Cecilia; Feregrino-Mondragón, Rocío Daniela; Robledo-Cadena, Diana Xochiquetzal; Sánchez-Thomas, Rosina; Jasso-Chávez, Ricardo; Saavedra, Emma; Marín-Hernández, Álvaro (Frontiers in Oncology, 2025)
IntroductionThe Krebs cycle (KC) is an important pathway for cancer cells because it produces reduced coenzymes for ATP synthesis and precursors for cellular proliferation. Described changes in cancer KC enzyme activities suggested modifications in the reactions that control the KC flux compared to normal cells.MethodsIn this work, kinetic metabolic models of KC of mitochondria from cancer (HepM), liver (RLM) and heart (RHM) to identify targets to decrease the KC flux were constructed from kinetic parameters (Vmax and Km) of enzymes here determined.ResultsThe enzymes Vmax values were higher in the following order: RHM > HepM > RLM; meanwhile, Km values were similar. Kinetic modeling indicated that the NADH consumption reaction (complex I) exerted higher control on the Krebs cycle flux in HepM versus RLM and to a lesser extent in RHM. These results suggested that cancer cells may be more sensitive to complex I inhibition than heart and other non-cancer cells. Indeed, cancer cell proliferation was more sensitive to rotenone (a complex I inhibitor) than heart and non-cancer cells. In contrast, cell proliferation had similar sensitivities to malonate, an inhibitor of succinate dehydrogenase, an enzyme that does not exert control.DiscussionOur results showed that kinetic modeling and metabolic control analysis allow the identification of high flux-controlling targets in cancer cells that help to design strategies to specifically inhibit their proliferation. This can minimize the toxic effects in normal cells, such as the cardiac ones that are highly sensitive to conventional chemotherapy.